(untitled) - Edgerton, Joel (Universal City, CA., 2017)
The story of Richard and Mildred Loving, an interracial couple, whose challenge of their anti-miscegenation arrest for their marriage in Virginia led to a legal battle that would end at the US Supreme Court.
Keywords: Tình yêu, Richard Perry,Loving, Richard Perry